A stitch in time: an unusual cause of enterovesical fistula. (19th September 2014) - O'Callaghan, John Matthew; Boyd, Jason Timothy; Singh, Anjana
Abstract : A 64-year-old woman with a history of a Stamey procedure for stress incontinence 20 years previously, underwent a diagnostic flexible cystoscopy to investigate recurrent urinary sepsis. Cystoscopic examination demonstrated a large vesicular calculus. When traction was applied to the calculus it was shown to be attached to a 10 cm length of non-absorbable suture material. The suture was attached to two further calculi, apparently originating from outside the bladder wall. All visible calculi and the suture were removed. In the following weeks the patient reported passage of air and faeculent material per-urethra. A repeat cystoscopy revealed an opening in the posterolateral bladder wall and CT confirmed the presence of an enterovesical fistula. Laparoscopy demonstrated a fistula between the terminal ileum and bladder wall. A further 10 cm length of non-absorbable suture material was removed from the terminal ileum and omentum. Laparoscopic repair of the fistula was performed successfully and the patient has remained symptom free following the procedure.